Introduction - constructing the modern fiscal states: ruptures, changes, and permanencies - Dominguez, Rodrigo da Costa (2023)
This introduction has a main goal: develop some key features of theory and the literature on state finance, establishing the bridges between the Portuguese Case and other European realities, followed by the case studies of other states in roughly chronological order, in order to preserve the volume’s cohesion and sequential coherence.